2014
DOI: 10.1007/978-3-319-12048-5_7
|View full text |Cite
|
Sign up to set email alerts
|

Current Medical Treatment of Glioblastoma

Abstract: Glioblastoma is the most common adult malignant primary brain tumor. Despite the advances in therapeutic options, survival of patients with glioblastoma remains dismal at 15-18 months. Current standard of care for newly diagnosed glioblastoma is maximal possible safe resection consistent with the preservation of neurologic function followed by concurrent temozolomide with radiation and adjuvant. Treatment options at recurrence include surgical resection with or without the placement of carmustine wafers, re-ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(64 citation statements)
references
References 54 publications
0
63
0
1
Order By: Relevance
“…Drugs considered most active are the temozolomide and fotemustine [12]. Antiangiogenic and particularly the bevacizumab appear promising but not used in first line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Drugs considered most active are the temozolomide and fotemustine [12]. Antiangiogenic and particularly the bevacizumab appear promising but not used in first line therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The processes of proliferation and invasion of malignant glioma cells are presumed to be mutually exclusive and the term Bgo or grow^has commonly been used to describe this behavior [22,58,64]. In previous investigations of this phenotypic axis, signaling molecules such as miRNAs and proteins have been characteristically revealed as monotonic regulators of growth or invasion [1,12,22,65].…”
Section: Discussionmentioning
confidence: 99%
“…[4] In addition to classic treatments, there are other adjuvant therapies such as glucocorticoids to reduce the peritumoral edema, antiangiogenic agents like bevacicumab (Avastin) which prolongs the progression-free survival; [5] However, a randomized trial showed that patients who consumed bevacizumab suffered from hypertension, thromboembolic events, intestinal perforation, and neutropenia. [6] Progressive brain volume loss have been observed with classic radio chemotherapy treatment resulting to neuropsychological changes in patients with glioblastoma.…”
Section: Current Cancer Therapy For Glioblastomamentioning
confidence: 99%